Proposed Business Model and Strategy Development for Radix Guitars - Wicaksono, Aditya; Toha, Mohamad (The Indonesian Journal of Business Administration, 2017)
Abstract â€“ Radix Guitars is a company engaged in the manufacturing industry with the main product is the guitar. Radix was founded in 2008, having previously used the brand Marlique. After eight years of operation, Radix realize that their business activities only from selling guitar and benefit less than optimal. Lack of brand awareness encourages Radix to formulate business strategy for the survival of its business. To address these issues, an analysis of external conditions using PEST analysis, Porter's Five Forces and Competitor Analysis. As for internal analysis, using VRIO framework analysis and examine business model canvas that is currently running by Radix. All of these analyses are summarized in SWOT analysis to be used as a basis for strategy formulation. Radix Guitars has competent resources to create quality products and face the competition. The formulation of a strategic move to develop business models and strategies will be scaling up competitiveness and brand awareness of consumers.Â Keywords: Guitar Manufacture, Business Strategy, Strategy Diamond